Titanium oxide nanoparticles fabrication, hemoglobin interaction, white blood cells cytotoxicity, and antibacterial studies. Issue 11 (24th July 2019) - Abdolmajid, Elham; Kharazi, Hasti; Chalaki, Mahfam; Khojasteh, Marzieh; Haghighat, Setareh; Attar, Farnoosh; Nemati, Fahimeh; Falahati, Mojtaba
Abstract: This study is focused on the fabrication and characterization of titanium oxide (TiO2 ) NPs. Afterwards; the interaction of TiO2 NPs with human hemoglobin (Hb) was investigated by FTIR spectroscopy, fluorescence spectroscopy, and molecular docking studies. Also, the cytotoxic effect of fabricated TiO2 NPs against human white blood cells (WBCs) was considered by MTT assay. The antibacterial effect of synthesized NPs was examined on Pseudomonas aeruginosa (ATCC 27853); Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 25923). TEM and DLS investigations showed that the synthesized TiO2 NPs have a narrow nano-sized distribution. XRD pattern of the fabricated NPs exhibited that the TiO2 NPs contain anatase phase. Similarity in amide I and II signal intensities showed that secondary structure of the adsorbed Hb is preserved. The intrinsic fluorescence study revealed that the fluorescence quenching of Hb was done by complex formation between Hb and TiO2 NPs trough the hydrogen bond and van der Waals interactions. Synchronous fluorescence spectroscopy determined that interaction of TiO2 NPs with Hb did not unfold the Hb structure in the vicinity of the Tyr and Trp residues. Molecular docking study depicted that Glu-95, Thr-134 and Tyr-140 are involved in the formation of hydrophilic bonds. MTT data and antibacterial assays indicated that TiO2 NPs endow distinguished antibacterial activities against Gram-negative and Gram positive strains at safe concentrations. This study may reveal that fabricated TiO2 NP can be used as a safe and potent antibacterial agent. Communicated by Ramaswamy H. Sarma